The effect of He-induced surface microstructure on D plasma-driven permeation through RAFM steel. (1st August 2022) - Wang, Lu; Zhou, Hai-Shan; Liu, Hao-Dong; Qi, Qiang; Tu, Han-Jun; Shi, Li-Qun; Luo, Guang-Nan
Abstract: The effect of helium (He)-induced surface microstructure on deuterium (D) plasma-driven permeation through a reduced activation ferritic/martensitic steel CLF-1 has been studied. CLF-1 steel was pre-exposed by He plasma with ion fluence of 10 22 –10 24 He m −2 and an incident energy of 100 eV at 708 K. The following D plasma-driven permeation experiment was performed at 693 K. Steady-state D permeation flux decreases with the increase in He ion fluence. D diffusion coefficient is not significantly affected by He pre-damage, while D reflection coefficient increases with the enhancement of He ion fluence. Scanning electron microscope and transmission electron microscope analyses clearly reveal the evolution of surface roughness and He bubble layer after He plasma exposure. Elastic recoil detection was used to identify He concentration depth profiles in the samples. Both the surface microstructure modification and He bubble layer formation contribute to the reduction of D permeation.